Pembinaan Keagamaan Bagi Siswa MTs Nurul Yaqin Kuala Kurun Dalam Rangka Pembentukan Karakter Religius - Amin, Zulva Sahrul Amin; Nurliana, Nurliana; Mustafa, Rani (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Religious formation was carried out with the aim of forming students' religious character. Service activities in the form of religious formation for MTs Nurul Yaqin Kuala Kurun students were carried out using a service learning (SL) approach. It was carried out in three meetings in March 2024 and was intended for MT Nurul Yaqin Kuala Kurun students in Classes VII, VIII, and IX, consisting of 52 students. This religious formation included guidance on prayer procedures and guidance on reading al-Qur'an, carried out in several stages, namely the delivery of material, the practice of worship, and questions and answers. The result showed that the religious formation was successfully implemented. It was shown by the increase in students' religious understanding regarding prayer procedures and reading al-Qur'an. The religious character shown by students after carrying out these activities was that they were increasingly obedient in carrying out worship, especially prayer and reading al-Qur'an.